INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN ATHLETICS IN THE CURRICULUM OF HIGHER EDUCATIONAL INSTITUTIONS (American Journal of Technology and Applied Sciences, 2023)
This article is about the correction of methods of preparing students Involved in athletics and, in particular, long-distance raise.